Education for Citizenship and Human Rights - Avelino Sarasúa Ortega (ADIDE Federación, 2008)
It seems perfectly natural to establish a parallel between the so-called Education for Citizenship and Human Rights subject and the social and civic competence. The official curriculum in every Spanish Autonomous Region is laid down by a Decree that makes it clear the relationship between that subject and the basic competence, and how the subject contributes to the acquisition and development of the competence. Then, why is Education for Citizenship and Human Rights questioned as a subject while the learning of the knowledge, abilities, values and attitudes necessary to achieve the basic social and civic competence is accepted without discussion?